Estudios del Trabajo desde el Sur. vol. IV - Julián Vejar, Dasten (Ariadna Ediciones, 2022)
The preparation of this book coincided with the end of two years of social coexistence in the midst of a global pandemic. This health reality has been thought, analyzed and addressed in the international literature through multiple axes (health systems, employment, care, daily life, etc.), reporting, as general conclusions, that we show a radicalization of pre-existing social inequalities in contemporary society. The situation represented a field of experimentation for capital, and an open scenario of overlaps and tensions between "life" and regimes focused on profits. The contradictions of establishing a sense of collaboration between the health of the population and the interests of companies, led to hard-fought and tense examples of ways to generate government practices focused on care, confinement and non-mobility. In the framework of these circumstances, the research task was also conditioned, when not affected. This book brings together a set of productions completed in recent years. Behind their different articles, motivations, expectations, reflections and silent experiences of how each of the authors made writing compatible in a pandemic context are intermingled.